MODEL PEMBELAJARAN TEAM GAME TOURNAMENT (TGT) MENINGKATKAN HASIL BELAJAR MACECIMPEDAN SISWA KELAS 5 SD N 2 PEDAWA - Ni Kadek Nia Prasetiawati; Ida Ayu Putu Purnami; I Wayan Gede Wisnu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve students' understanding of macecimpedan lessons using the Team Game Tournament (TGT) Learning Model for 5th grade students of SD N 2 Pedawa. This study uses qualitative and quantitative descriptive data. The subjects of this study were 5th grade students of SD N 2 Pedawa, and the object of research in this study was the Team Game Tournament (TGT) Learning Model. This research method uses a test sheet for each student in order to determine the students' abilities and understanding of macecimpedan lessons. This study obtained results, namely an increase in students' understanding when using the Team Game Tournament (TGT) Learning Model, namely from 66.87 to 83.12. The implications of this study are an increase in student learning when learning using the Team Game Tournament (TGT) Learning Model.